2013
DOI: 10.1590/s0100-39842013000600007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of occupational and patient dose in cerebral angiography procedures

Abstract: Objective: The present study was aimed at estimating the doses received by physicians and patients during cerebral angiography procedures in a public hospital of Recife, PE, Brazil. Materials and Methods: The study sample included 158 adult patients, and during the procedures the following parameters were evaluated: exposure parameters (kV, mAs), number of acquired images, reference air kerma value (K a,r) and air kerma-area product (P KA). Additionally, the physicians involved in the procedures were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…It is verified that the results obtained in the current study for staff 1 (the closest one) are much higher than in studies used for comparison, even the one performed in brain angiography (Lunelli et al, 2013) (an interventional procedure).…”
Section: Estimate Of Staff's Equivalent Dosessupporting
confidence: 80%
See 2 more Smart Citations
“…It is verified that the results obtained in the current study for staff 1 (the closest one) are much higher than in studies used for comparison, even the one performed in brain angiography (Lunelli et al, 2013) (an interventional procedure).…”
Section: Estimate Of Staff's Equivalent Dosessupporting
confidence: 80%
“…Both types of dosimeters were encapsulated in pairs in numerically identified plastic envelopes (as in Lunelli et al, 2013) made of the same intraoral film package used in dental radiology. This material allows the dosimeter to be sheltered from light and can be used on the patient in the region of the primary beam without causing any image distortion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 These combined factors may result in radiation doses that fall within permissible ranges 6 or potentially exceed the established safety thresholds for physicians and patients. 7 The effects of radiation include both stochastic and deterministic effects. Stochastic effects occur to a varying degree depending on the accumulated radiation dose received.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that, despite the benefits of these procedures, some deterministic effects can occur due to their complexity and long fluoroscopy times [1]. There are some studies of occupational radiation exposure [1,2] and some other recommendations regarding protective wear, especially for the performing clinician's eyes [3]. Recently, concern has grown especially for anaesthesiologists, as they are not considered occupationally exposed personnel.…”
Section: Introductionmentioning
confidence: 99%